Distributional preferences in adolescent peer networks - Simon Schürz; Yonas Alem; Martin Kocher; Frederik Carlsson; Mikael Lindahl (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2020)
We study distributional ("social") preferences in adolescent peer networks. Using incentivized choices between allocations for themselves and a passive agent, children are classified into efficiency-loving, inequality-loving, inequality-averse, and spiteful types. We find that pairs of students who report a friendship link are more likely to exhibit the same preference type than other students that attend the same school. The relation between types is almost completely driven by inequality-loving and spiteful types. Further analyses suggest that preference peer networks are mainly formed by selection into the network and, to a smaller degree, by preference transmission. The role of peer networks in explaining distributional preferences goes beyond network composition effects. A low rank in academic performance and a central position within the network relate positively to a higher likelihood of being classified as spiteful. Hence, social hierarchies seem to be correlated with distributional preference types.
Keywords: 330